Counseling on the Potency of Platelet Growth Factor in the Management of Ankle Sprain Trauma in Orthopedic Polyclinic Patients at YK Madira Hospital, Palembang, Indonesia - Luthfi, Kemas Abdul Mutholib; Hidayat, Rachmat (Indonesian Community Empowerment Journal, 2023)
Growth factors are not only capable of triggering cell and tissue repair but also act as anti-inflammatory molecules, capable of inhibiting inflammatory processes triggered by trauma. However, currently, patients with ankle sprains are still reluctant to get this therapeutic modality, even though the potential for this new therapeutic modality is superior enough to accelerate trauma repair. This is because the patient is still not familiar with this therapeutic modality. This community service aims to increase the knowledge aspect of ankle sprain patients about the potential benefits and possible risks of using platelet growth factors through the counseling and education process for ankle sprain patients at YK Madira Hospital, Palembang, Indonesia. The implementation of community service is carried out through 3 stages of the implementation process, namely preparation, implementation, and evaluation. The target audience for this community service activity is outpatients at the orthopedic polyclinic at YK Madira Hospital, Palembang, Indonesia. There is an enhancement knowledge score for respondents after being given counseling about the potential of growth factor from platelets to treat an ankle sprain, with p<0.05. The results of the study also showed that there was an increase in attitudes and behavior in choosing the modality of platelet growth factor therapy after the counseling process was carried out, with p <0.05. Counseling activities are effective in improving the knowledge and behavior aspects of patients at YK Madira Hospital, Palembang, Indonesia, in choosing the modality of growth factor therapy from platelets for ankle sprains.